Knockdown of long non‐coding RNA small nucleolar RNA host gene 9 or hexokinase 2 both suppress endometrial cancer cell proliferation and glycolysis. Issue 6 (5th April 2021) - Wang, Lianhua; Huang, Qiming; Lin, Qingqing; Chen, Lvxuan; Shi, Qiyang
Abstract: Aim: Endometrial cancer (EC) is a common type of malignant gynecological cancer. Small nucleolar RNA host gene 9 (SNHG9) has been discovered to serve a role in several types of cancer; however, the role of SNHG9 in EC remains unclear. The present study aimed to investigate the effects of lncRNA SNHG9 on cell proliferation and glycolysis in EC cells. Methods: SNHG9 and hexokinase 2 (HK2) mRNA expression levels were measured by reverse transcription‐quantitative PCR. Glucose consumption and lactate production were detected by the glycolysis cell‐based assay kit. Cell Counting Kit‐8 and colony formation assays were conducted to detect cell proliferation. The knockdown experiments of SNHG9 and HK2 were carried out by transfection of corresponding small interference RNAs (siRNA). The SNHG9‐overexpressed plasmid was transfected into the cells to upregulate SNHG9. HK2 protein levels were analyzed by western blotting assay. Results: SNHG9 expression levels were significantly upregulated in EC tissues and cells. The knockdown of SNHG9 subsequently effectively attenuated cell proliferation and glycolysis in vitro, while SNHG9 overexpression reported the opposite effects. Notably, the transfection of 2‐DG partially reversed the promoting effect of SNHG9 on glycolysis. Downregulation of HK2 markedly decreased cell proliferation and glycolysis in EC cells antagonized SNHG9. Conclusion: Either downregulation of SNHG9 or HK2 inhibits EC cell proliferation and glycolysis via repressing EC cell proliferation and glycolysis.